As sociedades anônimas e o direito de recesso como norma de proteção aos acionistas minoritários nas operações de incorporação: fundamentos normativos e adequação da lei vigente - Claudino, Gilbene Calixto Pereira (Universidade do Vale do Rio dos Sinos, 2022)
The "right of withdrawal" as an instrument to protect minority shareholders is pro-vided for in the Brazilian Corporate Law. This research seeks to understand how the demands related to this right have been applied when incorporations of corpo-rations occur. Investing in stocks requires the investor to make a preliminary analy-sis of the market and the risks that may be incurred when deciding to invest. These precautions must be taken in order to minimize investment risks. It is necessary to know a range of factors that can influence the investment. In this way, the study of the SOCIAL PURPOSE of the company, its market value, forms of redemption, value of dividends, possibility of lawsuits, are steps that can lead the investor to have more security when choosing to acquire assets of a certain com-pany. Although due precautions are taken before the decision to invest, the charac-teristic of dynamism inherent to publicly traded companies can lead companies to make decisions that bring about changes in their characteristics. These changes are not always compatible with the investor's perspective. In view of this fact and depending on the type of change occurred in the company, Law 6.404/1976, in its art. 137, provides for the shareholder's right of withdrawal, in the face of some spe-cific situations, such right consists of the possibility of the shareholder to withdraw from the company, also safeguarding the right to reimbursement of the invested amount (Art. 45, of Law 6,404/1976). The exercise of such prerogative will only be applied in the cases contemplated by the Law of Corporations, having the legislator described which the factual situations would give rise to its application because, otherwise, companies would run the risk of becoming financially unviable in the face of possible demands that could arise. IF this right was not delimited by law. The present work was based on Brazilian business doctrine, legislation, above all, the Corporate Law, as well as the jurisprudence of jurisdictional bodies such as STJ, TJDFT and TJRJ. The decisions brought were treated qualitatively, with an exploratory objective, using the bibliographic, documentary and retrospective doc-umentary procedure. The research in question sought to explore the historical line and the panorama of the stock market, highlighting the Corporations, identifying their peculiarities and the debates that guide this theme, as well as trying to under-stand how the institute of the right of withdrawal has been approached in the judi-cial instances. The quest to understand how the right of withdrawal has been ap-plied in practice, especially when incorporation occurs, necessarily involves the analysis of practical cases, with the objective of ascertaining the occurrence or not of broader interpretations of the law, or even limitations in relation to the scope of specific cases. Thus, it is imperative to know what the measures are to protect the minority shareholder and their application, providing greater security to the Market, contributing to its growth, meeting the desires and needs of society, with the securi-ty and guarantee of the application of the law.
Keywords: Sociedades anônimas; Direito de recesso; Acionista minoritário; Corporations; Right of withdrawal; Minority shareholder; ACCNPQ::Ciências Sociais Aplicadas::Direito